1992
DOI: 10.2527/1992.7072207x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro development of zygotes from prepubertal gilts after microinjection of DNA

Abstract: ABSTRACT:The effect of pronuclear microinjection of DNA and culture in excised mouse oviducts on the development of porcine zygotes was assessed in this study. Precocious ovulation was induced in prepubertal gilts with pregnant mare's serum gonadotrophin and hCG. Zygotes received either pronuclear microinjection of buffer alone, buffer containing a DNA construct, or no microinjection. Zygotes were cultured in vitro in either modified Krebs-Ringer bicarbonate medium (KRBI for 144 h or in mouse oviduct (MO) expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…This result is in agreement with early reports for mice (16), pigs (32), and cattle (18,19). These studies suggest that microinjection may reduce initial cleavage rates by damaging the pronucleus of the zygote (24).…”
Section: Discussionsupporting
confidence: 83%
“…This result is in agreement with early reports for mice (16), pigs (32), and cattle (18,19). These studies suggest that microinjection may reduce initial cleavage rates by damaging the pronucleus of the zygote (24).…”
Section: Discussionsupporting
confidence: 83%
“…The DNA injected at late pronuclear stages may be available for integration during this second replication event. Williams et al (1992) demonstrated that the decrease in developmental efficiencies of DNA-injected embryos was due to the DNA itself, not the injection procedure. The extent of the ability of the embryo to repair damage from micromanipulation at different pronuclear stages is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Oviducts were exteriorized by midventral laparotomy. A retrograde oviductal flush was performed from the utero-tubal junction to the infundibulum with 20 mL of Beltsville Embryo Culture Medium (V. G. Pursel, personal communication), a HEPES-buffered medium for handling embryos in air (Williams et al, 1992b).…”
Section: Methodsmentioning
confidence: 99%
“…1994. 72:1299-1305 A culture system able to support adequate development of porcine embryos microinjected with DNA to the blastocyst stage needs to be refined (Williams et al, 1992b). Among the best development rates for noninjected embryos reported thus far, Krisher et al (1989) found close t o 80% development to the morula or blastocyst stage for one-cell porcine embryos cultured in mouse oviductal explants.…”
Section: Introductionmentioning
confidence: 99%